IMPACT OF PRE-EXISTING HYPERTENSION ON THE DEVELOPMENT AND OUTCOMES OF PERIPARTUM CARDIOMYOPATHY - HASSAN, K; FAROOQ, A; REHMAN, AU; HASSAN, L; HASSAN, T (Biological and Clinical Sciences Research Journal, 2024)
An uncommon but dangerous heart ailment known as peripartum cardiomyopathy (PPCM) may develop in the last month of pregnancy or during the first five months after giving birth. It has been shown that pre-existing hypertension is one risk factor that might make PPCM more severe. The purpose of this research is to assess how pre-existing hypertension affects the course, clinical manifestation, and results of PPCM. Objective: To evaluate the impact that pre-existing hypertension has on the clinical course, echocardiographic results, and maternal outcomes in PPCM maternal cases. Methods: At the DHQ Hospital KDA, Kohat, a retrospective cohort study was carried out between September 2023 and August 2024. There were 56 women with PPCM in total; 28 of them had pre-existing hypertension and the other 28 did not. Data on demographics, clinical conditions, and echocardiograms were gathered. The two groups' maternal outcomes—heart failure progression, recovery of left ventricular function, and problems after childbirth—were compared. SPSS version 26 was used for data analysis, and a p-value of less than 0.05 was deemed statistically significant. Results: Comparing women with pre-existing hypertension to the non-hypertensive group, they showed considerably higher rates of heart failure progression (39% against 21%, p = 0.04) and significantly lower left ventricular ejection fraction (LVEF) at diagnosis (30.1% versus 35.5%, p = 0.01). Women with hypertension were more likely to have persistent LVEF impairment (36% vs 18%, p = 0.03). Additionally, the group with hypertension saw higher readmission rates (25% vs 10.7%, p = 0.02). Conclusion: A substantial risk factor for unfavourable outcomes in PPCM, such as reduced heart function and increased rates of postpartum problems, is pre-existing hypertension. Improving PPCM results for hypertensive women requires closer observation and focused care.